2020
DOI: 10.1055/a-1149-1700
|View full text |Cite
|
Sign up to set email alerts
|

Utility of laser-cut covered self-expandable metal stents for unresectable malignant distal biliary obstruction: a single-center experience

Abstract: Background Few reports have evaluated the effectiveness of laser-cut, covered, self-expandable metal stents (LC-CSEMS) for unresectable malignant distal biliary obstruction (MDBO) and whether reintervention is feasible after placement. We describe our experience with LC-CSEMS placement for unresectable MDBO. Methods Patients undergoing LC-CSEMS placement for unresectable MDBO from November 2014 to December 2018 were reviewed. Recurrent biliary obstruction (RBO), median time to RBO (TRBO), and reinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Isayama et al and Marui et al reported stent migration rates of 12% and 4%, respectively. 35,37 However, the migration rate of the laser-cut-type CMSs remains unclear. Furthermore, few studies have examined whether the anti-migration features of biliary SEMSs prevent migration.…”
Section: Discussionmentioning
confidence: 99%
“…Isayama et al and Marui et al reported stent migration rates of 12% and 4%, respectively. 35,37 However, the migration rate of the laser-cut-type CMSs remains unclear. Furthermore, few studies have examined whether the anti-migration features of biliary SEMSs prevent migration.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study by Marui et al, the authors have not used small-sized SEMS and they have not explored their benefits in hilar strictures, which require further exploration. 15 In this study, all except one LC-CSEMS were removed with snare or rat tooth forceps which points their potential use even in patients with benign biliary strictures.…”
Section: Commentarymentioning
confidence: 94%
“…Marui and colleagues, in a retrospective, observational, single-center study, explored a newer laser-cut FCSEMS (LC-CSEMS) for unresectable malignant distal biliary obstruction. 15 The new LC-CSEMS (X-Suit NIR covered biliary metal stent; Olympus Medical Systems, Tokyo, Japan) is 10 mm in diameter and 8 or 10 cm in length. 15,16 The stent has unique zigzag design composed of thick and thin struts made of nitinol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the advantage of the covered self-expandable metal stent is easy removal, it is thought that performing endoscopic removal of the laser-cut-self-expandable metal stent in cases of recurrent biliary obstruction is difficult due to its stent structure compared to that of the braided-covered self-expandable metal stent. However, recent studies have shown the possibility of endoscopic removal of the laser-cut self-expandable metal stent [ 48 , 49 , 50 , 51 ]. Moreover, the newly developed laser-cut-self-expandable metal stent, which has an anti-reflux valve to prevent duodenobiliary reflux, has been reported to be useful for patients with unresectable distal malignant biliary obstruction [ 52 , 53 ].…”
Section: Palliative Biliary Drainage For Patients With Unresectable Distal Malignant Biliary Obstructionmentioning
confidence: 99%